Student-Teacher Relationships of Children with Autism Spectrum Disorder: Distinct Contributions of Language Domains - Feldman, Melanie (Res Dev Disabil, 2019)
BACKGROUND AND AIMS: High quality student-teacher relationships (STR) are important for children’s academic and social development. We explore how individual child language domains (semantics, syntax, pragmatics), teacher years of experience, and classroom placement (general or special education) relate to STR quality for children with autism spectrum disorder (ASD) across the school year. METHODS AND PROCEDURES: 191 children with ASD (M(age) = 5.6 years) completed a standardized language assessment and their teachers reported on STR quality twice during the school year. OUTCOME AND RESULTS: Pragmatics, but not semantics or syntax, had a direct effect on student-teacher closeness. The association between semantics and closeness was moderated by classroom type; for students with low semantics, teacher-reported closeness was lower in general versus special education. Teachers in special versus general education classrooms reported closer relationships. More experienced teachers reported closer and less conflictual relationships. None of the three language domains were associated with student-teacher conflict. CONCLUSIONS AND IMPLICATIONS: Pragmatic and semantic language skills were associated with closer relationships. Language-focused therapies may be effective in carrying over to impact STR quality. Given the stability in relationship quality, targeted interventions should be delivered to teachers at the beginning of the school year to support positive relationship development.